The impact of trans-sacral epiduroscopic laser decompression on quality of life in lumbar disc herniation - Ozcan, Sibel; Muz, Arzu; Altun, Aysun Yildiz; Payam, Rustem; Polat, Mehmet Fatih; Onal, Selami Ates (Kare Publ, 2024)
Objectives: Trans-sacral epiduroscopic laser decompression (SELD), employing a video-guided catheter and laser, is one of the preferred options for minimally invasive treatment in lumbar disc disease. The aim of this study was to evaluate the effect of SELD treatment on pain, disability, and quality of life in patients with lumbar disc herniation. Methods: Between January 2015 and June 2017, a total of 76 patients who underwent SELD were examined retrospectively. The Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) scores were recorded preoperatively, as well as 1, 3, 6, and 12 months after SELD. Quality of life was recorded preoperatively and 12 months after SELD. Patient satisfaction was evaluated based on Odom's Criteria at the final follow-up. Results: Improvement was observed in low back pain and radicular pain, with the VAS score decreasing from 6.5 +/- 0.9 and 7.2 +/- 0.3 to 2.31 +/- 1.6 and 2.9 +/- 1.3 at the final follow-up (p<0.001). The rate of disability, assessed by ODI, decreased from 65.21 +/- 1.7 to 21.38 +/- 1.0 at the final follow-up. SF-36 scores were statistically higher for all sub-variables of the questionnaire after the procedure. At the final follow-up, 65.8% of patients reported a degree of satisfaction as excellent-good based on Odom's Criteria. Conclusion: Trans-sacral epiduroscopic laser decompression enhances quality of life by improving pain and disability scores in patients with chronic low back and/or radicular pain who do not respond to conservative treatments and epidural steroid administration.
Keywords: Epiduroscopy; lumbar disc herniation; quality of life; VAS